Tree drawing test as an auxiliary tool for evaluating schizophrenia treatment outcomes - Liu, Yige; Yuan, Junmei; Zhang, Yanfei; Jin, Hui; Gao, Li; Liu, Wei; Liu, Guorui (Frontiers in Psychiatry, 2025)
ObjectiveThis study aimed to investigate the changes in quantitative indicators of the Tree Drawing Projection Test across different treatment stages in patients with schizophrenia, in order to provide an objective basis for evaluating treatment efficacy.MethodsA self-controlled study design was employed. Sixty patients with schizophrenia underwent the Tree Drawing Projection Test at three time points: Week 1, Week 13, and Week 37. Differences in drawing indicators were analyzed across these time points.ResultsAmong patients with schizophrenia, the values of crown area, crown height, crown width, trunk area, and trunk height gradually increased from Week 1 to Week 37, showing observable differences (p <0.05). In patients with a disease course of less than 10 years, the changes in trunk area, trunk height, and trunk width during the acute treatment period (Week 1 to Week 13: 5.66 ± 0.55, 2.18 ± 0.20, 0.68 ± 0.08, respectively) were significantly greater than those in patients with a disease course exceeding 10 years (p <0.05). At Week 13, schizophrenia patients showed significant differences compared with healthy controls in crown area (99.67 ± 10.89), crown width (11.99 ± 2.15), trunk area (23.94 ± 4.23), trunk width (4.33 ± 0.92), root area (6.43 ± 1.61), and root height (0.76 ± 0.07) (p <0.05).ConclusionIn schizophrenia patients, quantitative indicators of the Tree Drawing Projection Test—specifically crown area, crown height, and crown width—demonstrated steady increases across Week 1, Week 13, and Week 37, with these changes being statistically significant. These findings suggest that the Tree Drawing Projection Test can serve as a useful tool for assessing clinical treatment efficacy in schizophrenia.